Scaling Brief #4: Scaling glossary - CGIAR (Deutsche Gesellschaft für Internationale Zusammenarbeit, 2020)
This scaling brief was developed by CGIAR Science Leaders and scaling specialists to provide guidance for the design and implementation of major CGIAR initiatives (see Brief #1 for more background information). It explains key terms of relevance, building on those already recognized by the CGIAR, and which are used in Brief #2 on principles and Brief #3 on approaches and tools. The glossary builds partly on definitions provided by the CGIAR 2030 Research and Innovation Strategy and the CGIAR glossary of terms for monitoring, evaluation, learning, and impact assessment.